Advances in longitudinal survey methodology - Lynn, Peter, 1966- (Wiley series in probability and statistics., 2021)
"The methodology of longitudinal surveys is a specialist topic which has evolved from the field of survey methodology. Survey methodology itself has evolved over the last century or so, with an early focus on sampling theory (1890s to 1940s), followed by attention to question and questionnaire design (1940s to 1970s) and obtaining respondent participation (1980s to 2000s). More recent developments included web survey methods and mixed mode methods, other uses of new technologies, data linkage, the use of paradata. Though the first longitudinal surveys began in the 1960s, such surveys were rare until the 1980s. Researchers became increasingly aware of various unique features and opportunities of longitudinal surveys and methodological research into these unique features developed rapidly throughout the 1990s and 2000s. The data produced by longitudinal surveys allow researchers to better understand dynamic processes of change, including processes of cause-and-effect, that can barely be addressed by data from cross-sectional surveys. An understanding of the implications of the methodological options available for the design and implementation of such surveys will help researchers to produce better longitudinal data in future."--